Isti’arah Tamthiliyah Dalam Tafsir Kitab Ruh Al-Bayan Karya Isma’il Haqqi - Fitria Ulva (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2022)
This research is a research library research, with a historical-factual approach related to the thoughts of the characters. Researchers used descriptive, holistic, and interpretation methods. So that the researcher examines the book of ruh al-bayn which specifically discusses isti'arah tamthiliyah, books and books that discuss isti'arah and articles that support this discussion.Based on the results of research conducted by the author, the views of commentators on literature, especially about isti'arah tamthiliyah have good attention, even though the book of ruh al-bayn has a deep Sufistic style, this is motivated by mufassir thought who is also an expert in several scientific fields, especially balaghah which makes the book ruh al-bayn have a fairly complete interpretation, and avoids liberal and undirected thinking so that people know the meaning of the Qur'an and not fixated on the original meaning of lafaz which causes a contradiction to the meaning contained in the Qur'an.